Psychosocial distress in people with overweight and obesity: the role of weight stigma and social support - Vladimira Timkova; Pavol Mikula; Iveta Nagyova (Frontiers in Psychology)
We aimed to assess the role of weight stigma and social support in depression, anxiety, and loneliness controlling for sociodemographic and clinical variables. A total of 189 adults with overweight/obesity were included. Participants were recruited from outpatient clinics by general practitioners which covered all regions of Slovakia. Correlation analyses and multiple linear regression were used to analyze the data. Participants experienced weight-related teasing (40.4%), unfair treatment (18.0%), and discrimination (14.1%). We found an association between lower age, female sex and psychological distress. No role of obesity indicators in psychosocial distress was identified, except for a small association between body mass index and depression in correlation analyses. Significant associations between experienced weight stigma/self-stigmatization and psychosocial distress weakened when variables related to the social support system were added to the linear regression. Poor social support was strongly associated with depression, anxiety, and loneliness. The explained variance in the final regression models was 42, 44, and 54%, respectively. Weight stigma negatively affects mental health and a sense of belonging while it seems to be a more significant contributor to psychosocial distress compared to obesity per se. Interventions targeting weight-related self-stigmatization and social relationships may mitigate the negative impact of weight stigma on psychosocial well-being.